Real-time fluorescent multiple cross displacement amplification for rapid and sensitive Mycoplasma pneumoniae detection - Xiao, Fei; Zhang, Yu; Xu, Wenjian; Fu, Jin; Huang, Xiaolan; Jia, Nan; Sun, Chunrong; Xu, Zheng (Frontiers in Cellular and Infection Microbiology, 2024)
Mycoplasma pneumoniae is a significant pathogen responsible for community-acquired pneumonia, predominantly affecting children and adolescents. Here, we devised a rapid method for M. pneumoniae that combined multiple cross displacement amplification (MCDA) with real-time fluorescence technology. A set of ten primers, which were specifically designed for M. pneumoniae detection, were employed in a real-time fluorescence MCDA reaction. Of these, one primer incorporated a restriction endonuclease recognition sequence, a fluorophore, and a quencher, facilitating real-time fluorescence detection. The real-time (RT)-MCDA reactions were monitored in a simple real-time fluorescence instrument and conducted under optimised conditions (64°C for 40 min). The detection limit of the M. pneumoniae RT-MCDA assay for genomic DNA extracted from M. pneumoniae culture was down to 43 fg/µl. This assay accurately identified M. pneumoniae strains without cross-reacting with other bacteria. To validate its practical application, we tested the M. pneumoniae RT-MCDA assay using genomic DNA extracted from clinical samples. The assay’s detection capability proved comparable with real-time PCR, MCDA-based biosensor detection, and visual inspection under blue light. The entire process, including rapid DNA extraction and real-time MCDA detection, was completed within 1 h. Overall, the M. pneumoniae RT-MCDA assay reported here is a simple and effective diagnostic tool for rapid M. pneumoniae detection, which holds significant potential for point-of-care testing and in resource-limited regions.